Answer:
its the second option
Step-by-step explanation:
4x - 5y = -12
-x + 5y = 18
Add the equations together:
4x + -x = 3x
-5y + 5y = 0
-12 + 18 = 6
So now you have:
3x = 6
Divide both sides by 3:
X = 2
Now you have the value of x, replace x with 2 in one of the equations and solve for y:
4(2) -5y = -12
8 -5y = -12
Subtract 8 from both sides:
-5y = -20
Divide both sides by -5:
Y = 4
The solution is x = 2 and y = 4 which is written as (2,4)
Answer:
The value of f(g(3) = 1,008
Step-by-step explanation:
<u>Step:-1</u>
Given f(x) =![3 x ^ 2 + 2 x](https://tex.z-dn.net/?f=3%20x%20%5E%202%20%2B%202%20x)
and g(x) = 3x+9
h(x) = 12+x
Given g(x) = 3x+9
put x =3
g(3) = 3(3)+9
<u> g(3) = 18</u>
<u>Step :-(2)</u>
f(g(3)) = f(18)
f(g(3) = 3(18)^2 +2(18) (since f(x) =
)
= 1,008
<u>Final answer</u>:-
The value of f(g(3) = 1,008
Answer:
⇒ answer 1
Step-by-step explanation:
* Lets explain how to find the inverse of a function
- To find the inverse of a function :
# Write y = f(x)
# Switch the x and y
# Solve to find the new y
# The new y is ![f^{-1}](https://tex.z-dn.net/?f=f%5E%7B-1%7D)
* Lets solve the problem
∵ f(x) = 2x + 1
- Put y = f(x)
∴ y = 2x + 1
- Switch x and y
∴ x = 2y + 1
- Solve to find the new y
∵ x = 2y + 1
- Subtract 1 from both sides
∴ x - 1 = 2y
- Divide both sides by 2
∴ (x - 1)/2 = y
- Divide each term in the left hand side by 2
∴ y = 1/2 x - 1/2
- Replace y by ![f^{-1}](https://tex.z-dn.net/?f=f%5E%7B-1%7D)
∴ ![f^{-1}(x)=\frac{1}{2}x-\frac{1}{2}](https://tex.z-dn.net/?f=f%5E%7B-1%7D%28x%29%3D%5Cfrac%7B1%7D%7B2%7Dx-%5Cfrac%7B1%7D%7B2%7D)
* The inverse of the function is ![f^{-1}(x)=\frac{1}{2}x-\frac{1}{2}](https://tex.z-dn.net/?f=f%5E%7B-1%7D%28x%29%3D%5Cfrac%7B1%7D%7B2%7Dx-%5Cfrac%7B1%7D%7B2%7D)
Answer:
The distance between the two points is 13 units.
Step-by-step explanation:
take the test